Внедрение оксикарбонитрирования взамен твердого хромирования - Коробочка, О. Н.; Чернета, О. Г.; Волощук, Р. Г. (НТУ "ХПИ", 2015)
В данной работе рассматривается: исследование и освоение новой низкотемпературной химико-термической обработки (оксикарбонитрирования), взамен хромирования для деталей: шток амортизатора; крышка цилиндра; плунжера рабочего домкрата. Сущность процесса заключается в создании на поверхности деталей слоя, обогащенного азотом и углеродом с последующим его контролируемым окислением. Проведенные сравнительные коррозионные испытания, а также испытания на износ показали значительное увеличение коррозионной стойкости и повышенную износостойкость деталей после оксикарбонитрирования по сравнению с деталями, подвергнутыми твердому хромированию.

The aim of this work is to study and development of new low-temperature chemical heat treatment (oksikarbonitrirovaniya) instead of chrome plating for details: shock-absorber rod; cylinder cover; plunger working jack. The essence of the process consists in creating on the surfaces of the layer enriched with carbon and nitrogen, followed by a controlled oxidation. Conducted comparative corrosion tests, as well as the wear test showed a significant increase in corrosion resistance and high wear resistance parts after oksikarbonitrirovaniya compared with the items subjected to hard chrome plating. In order to improve the wear resistance within the surface cap molded into an existing design bronze bushing. This process is rather laborious and requires the use of extremely scarce nonferrous metals. To improve the efficiency of the mating parts "shock-absorber rod - cylinder cover" is useful when oksikarbonitrirovanii piston rod similar coating used for the cylinder head. Surface treatment of the cylinder head oksikarbonitrirovaniem, would eliminate the costly bronze bushing.
Introduction to replace hard chrome plating oksikarbonitrirovaniya
Keywords: испытания; микротвердость; микроструктура; износ; testing; microhardness; microstructure; wear; tear